Factors Associated with Physical Activity in People with Diabetes - Ewa Głowacka; Agnieszka Latkowska; Elżbieta Sieńko-Awieraniów; Marta Stępień-Słodkowska (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
Background: Diabetes mellitus is a chronic disease related to the occurrence of numerous metabolic disorders. Their common feature is hyperglycaemia, caused by insufficient insulin secretion or its malfunction. The World Health Organization states that 346 million people worldwide have diabetes. The studies in adults with type 2 diabetes clearly demonstrate that the change of lifestyle behaviours effectively improves glycemic control. The modifications of lifestyle habits, such as regular physical activity and healthier dietary habits prove to be beneficial for patients. The aim of this study was to determine the factors affecting the level of physical activity in people with diabetes mellitus. Methods: Research material consisted of the data gathered from a diagnostic survey, which was conducted in a form of a questionnaire. The study included 60 people with type 1 or type 2 diabetes. Results: Unfortunately, the results show that not all of them were active enough, which is so crucial for stabilizing the disease. Conclusions: The diagnosis of diabetes in the respondents resulted in more time being spent by them on physical activity, which resulted in the improvement of diabetes control and the normalization of body weight according to BMI, thus increasing the effectiveness of diabetes treatment and reducing complications. The frequency of the physical activity undertaken by the respondents prior to the disease was not related to gender, however, after the diagnosis, it was dependent on gender